The impact of Daniel's educational model on the development of historical thinking among fourth grade literary students (Journal of the College of Basic Education, 2022)
Educators confirm that there are problems that concern all workers in the educational field, including the problem of the low level of student achievement in formal education in Iraq and the Arab world, and it may be the adoption of old methods of teaching based on memorization and information preservation, and this calls for searching for alternative teaching methods, which confirms that The results of some studies and research that dealt with the issue of achievement among students, including, for example, the study of (Al-Shukraji 2005), the study of (Al-Bawi 2007), and the study of (Zayadat 2007).Another problem identified by many studies has also emerged, which is the inability of students in the preparatory stage to practice the skills of thinking, investigation and problem-solving, including a study (Al-Jundi, 2002).